Embedded System Simulation for Electrical Hardware Test Virtualization - István Szalay; Ferenc Péter Speiser; Dénes Fodor (Chemical Engineering Transactions)
In the automotive industry, the reduction of development costs has a key importance. Also, the duration of the development is a significant aspect. Electrical hardware development is an expensive, time-consuming process with a lot of development stages (e.g., prototypes, electrical tests, mechanical tests, lifecycle tests). Virtualization is an important factor in making electrical component development more sustainable; using this method, less prototype manufacturing is necessary since the simulations make it faster and more effective to find out a large portion of possible faults without building a hardware prototype. The main goal of the paper is to explore the capabilities of seven software solutions that can manage the virtualization of the electrical development toolchain. The simulation environment should manage the simulation of the electrical circuit, including the sensors and loads, the microcontroller, and the execution and debugging of the uploaded program code. The study provides guidance on choosing the proper simulator depending on the simulation focus.